Formulation design, optimization & in vitro evaluation of novel orodissolving tablets of efavirenz for hiv infections - Ayyappan, T; Poojitha, C; Vetrichelvan, T (Bangladesh Journal of Scientific and Industrial Research, 2015)
In the present work, orodissolving tablets of Efavirenz were prepared by direct compression method with a view to enhance patient compliance. A 23 full factorial design was applied to investigate the combined effect of three formulation variables. Amount of crospovidone, croscarmellose sodium and sodium starch glycolate were used as superdisintegrant material along with direct compressible mannitol to enhance mouth feel. The prepared batches of tablets were evaluated for hardness, friability, weight variation, disintegration time, wetting time, drug content and in-vitro dissolution studies. Based on wetting time, disintegration time, the formulation containing crospovidone (5% w/v), carscarmellose sodium (5% w/v) and sodium starch glycolate (8% w/v) was found to be promising and tested for in-vitro drug release pattern (in 0.1 N HCl), short term stability and drug- superdisintegrants interaction. Surface response plots are presented to graphically represent the effect of independent variables (conc. of superdisintegrants) on the in-vitro dissolution time. The validity of the generated mathematical model was tested by preparing extra-design check point formulation. The formulation showed nearly faster drug release compared to the conventional commercial tablet formulation. Stability studies on the optimized formulation indicated that there was no significant change found in physical appearance, hardness, disintegration time, drug content and in-vitro drug release. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22131 Bangladesh J. Sci. Ind. Res. 49(3), 173-180, 2014